Investigations into Magic, an Edition and Translation of Martín Del Río’s Disquisitionum magicarum libri sex - Maxwell-Stuart, Peter, author.
1 online resource.
Keywords: Martín Del Río (1551-1608) was a remarkably learned Jesuit scholar. His prolific output includes six volumes of Investigations into Magic which sought to be the last word on magic, witchcraft, and allied subjects such as divination and superstition, and a detailed manual of advice for judges and confessors engaged in combatting what was seen at the time as a dangerous threat to the spiritual life of humanity in this world and the next. First published in 1599-1600, Investigations was heralded as a major contribution to the armoury of the Counter-Reformation, and went through several editions, the last appearing in 1747.